Analisa Proses Bisnis Klien dan Pelatihan Web by Learning - Hayashi, Richard Randy; Ananda, Denta Felli (Jurnal Abdimas Sosial, Ekonomi, dan Teknologi, 2023)
This internship report is intended to explain the author's activities in the independent internship process at PT Ernst & Young Indonesia. This program provides an opportunity to gain work experience and contribute to the company where the internship is conducted. This report will explain the daily activities as part of the People Advisory Services division. This project was carried out for a client in a company in the financial industry in Indonesia to analyze gaps, potential, risk control and improve business processes as well as its organizational structure. Therefore, client companies use the services of EY consultants to carry out model operations, organization designs and transformation designs. This project work results in useful deliverables for EY clients and provides interns a wealth of knowledge and experience.